PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X IPA 1 SMA NEGERI 2 PEKANBARU - Raufany, Gema; Solfitri, Titi; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was classroom action research that aims to improve learning process and to increase student mathematics achievement with applied the learning model of Problem Based Learning. The subject of this research is student of class X IPA 1 SMA Negeri 2 Pekanbaru in academic years 2017/2018, which amounted to 36 students, consist of 17 boys and 19 girls. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. The instruments of data collection in this research were observation sheets and students mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students mathematic tests were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. Most of students were very confidenced and actived in learning process, such as while they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. The results of this study indicate the number of students who reached Minimum Mastery Criteria of knowledge increase from basic score to quiz-I and quiz-II. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (16,7%) to the first quiz (44,4%) to the second quiz (55,6%). For the skills of basic score the first quiz (30,6%) to the second quiz (50%), thus it can be concluded that the application of Problem Based Learning can improve learning process and increase mathematics achievement from the students at class X IPA 1 SMA Negeri 2 Pekanbaru in academic years 2017/2018 for the subject rational and irrational inequalities and linear equations of three variables.Key Words: Students’ Mathematic Achievement, Problem Based Learning, Class Action Research